Influence of sales growth, profitability, asset structure, company size, and free cash flow on debt policy - Dewi, Gita Primadhany Mutiara; Kusumawati, Eny (Indonesia Auditing Research Journal, 2024)
Debt policy plays a role in a company as a means of obtaining funds regulated by corporate governance, both internal and external. This research explores how debt policy in non-financial firms listed on the Indonesia Stock Exchange from 2020 to 2022 is influenced by factors such as sales growth, profitability, asset structure, firm size, and free cash flow. Employing purposive sampling, the study identified 648 companies that met the necessary criteria for observation. The analysis was conducted using multiple linear regression. The findings reveal that both profitability and firm size significantly impact debt policy. In contrast, sales growth, asset structure, and free cash flow do not show a significant effect on debt policy.